Искусство бронзового века: погребальный ритуал - Иванова, С.В. (Материалы по археологии Северного Причерноморья, 2009)
In this. work goes about some aspects of world outlook submissions of tribes of Bronze Age. А burial mound is the information generator of the most different level. So, а funeral ceremony is perceived bу many researchers as «text» (in semiotic sense ), and his elements ~ as signs. The view of death act is important part in constrцcting of world outlook which inherent any social cultural community. The death exactly is а. central event in life of archaic society, allowing to Ье attached to the sacral world. The ceremonies ofburial in the Bronze Age could include different components of art. They linked with dance (how Ьу the sign system of communication), and with shamanism, and with agon. The art as mean of information transfer submits to the laws of the semiotic systems. The early forms of art were associated not only with the receipt of aesthetic pleasure, but, maybe, even in а greater degree served for the transmission of sacral experience.